Synthesis and Characterization of Non-Toxic Thermal Stabilizers of PVC Based on Layered Double Hydroxides - Park, Eunju; Lee, Jinae; Wook Park, Hyung (Asian Journal of Chemistry, 2014)
Hydrotalcite-like compounds are expressed by the general formula [M(2+)1xM(3+)x(OH)2]x+1An-x/ n·mH2O, where M(2+) and M(3+) are divalent and trivalent cations, respectively. Mg1-xAlx(OH)2COn-x/ n·mH2O structures, non-toxic thermal stabilizers of poly(vinyl chloride), were manufactured by various coprecipitation methods to optimize the manufacturing process of non-toxic thermal stabilizers of poly(vinyl chloride). These hydrotalcite-like compounds were characterized by field-emission-scanning electron microscopy, X-ray diffraction, thermal analysis and transmittance spectra. Samples were fabricated using different steps and a base reactant produced the most stable sample. The cell parameter c is related to the thickness of the brucite-like layer and the interlayer distance was 23.21 Å.